Truncating tau reveals different pathophysiological actions of oligomers in single neurons - Emily Hill (Nature Portfolio, 2021)
Hill et al. examine the effects of full-length or truncated human recombinant tau on the excitability of hippocampal pyramidal neurons in mice. Their results suggest that effects seen with full-length tau oligomers can be dissected apart using tau truncations and highlights a tau-mediated alteration in voltage-gated sodium channel currents.